Delayed fear extinction in individuals with insomnia disorder. Issue 8 (31st May 2018) - Seo, Jeehye; Moore, Kylie N; Gazecki, Samuel; Bottary, Ryan M; Milad, Mohammed R; Song, Huijin; Pace-Schott, Edward F
Abstract: Study Objectives: Insomnia increases the risk for anxiety disorders that are also associated with fear-extinction deficits. We compared activation of fear and extinction networks between insomnia disorder (ID) without comorbidity and good sleepers (GS). Methods: Twenty-three ID participants age- and sex-matched to 23 GS participants completed 14 days of actigraphy and diaries, three nights of ambulatory polysomnography and a 2-day fear conditioning and extinction paradigm. Fear conditioning and extinction learning occurred on the first day, followed 24 hours later by extinction recall. Blood-oxygen-level-dependent functional magnetic resonance imaging (fMRI) signal and skin conductance responses (SCR) were recorded. Nineteen participants per group produced usable fMRI data. Beta weights from areas where activation differed between groups were regressed against sleep and psychophysiological measures. SCR was compared between groups at various stages of the paradigm. Results: During fear conditioning, both ID ( N = 19) and GS ( N = 19) activated fear-related structures. Across extinction learning, ID ( N = 19) demonstrated little change, whereas GS ( N = 16) activated both fear and extinction-related areas, including the hippocampus, insula, dorsal anterior cingulate (dACC), and ventromedial prefrontal (vmPFC) cortices. During extinction recall, while GS ( N = 17) demonstrated limited activation, ID ( N = 16) activated regions similar to those previously activated in GS (vmPFC, dACC, insula). Sleep quality was predictive of activations seen at various stages of the paradigm. SCR data suggested ID were more physiologically reactive than GS. Conclusions: Across extinction learning, GS but not ID activated both fear and extinction-related networks. At extinction recall, ID engaged similar regions whereas GS no longer did so. Individuals with ID may show a delayed acquisition of fear extinction memories.